Optimalisasi Implementasi Asuhan Keperawatan Primer - Sumampow, Meylly; Novieastari, Enie; Rachmi, Shanti Farida; Yatnikasari, Aat; Kamil, Hajjul (Journal of Telenursing (JOTING), 2023)
This research aims to optimize the application of primary nursing care methods, which positively impact nursing care services for patients and nurses. This research method uses a case study approach with interviews, observations, document reviews, and surveys and uses fishbone analysis for problem analysis. The research results show that the implementation of primary nursing care methods in hospitals can be optimized by increasing human resources (all nursing staff) in terms of understanding and increasing knowledge, which is updated regularly, improving the organizing, monitoring, and evaluating functions of room heads and increasing the role of primary nurses as preceptors. In conclusion, increasing nursing human resources in understanding and expanding regularly updated knowledge can maximize the application of direct nursing care. Keywords: Analysis, Nursing Care, Primary Nursing Model, Nurse Manager, Hospital